Climate-Smart Conservation Agriculture, Farm Values and Tenure Security: Implications for Climate Change Adaptation and Mitigation in the Congo Basin - Molua, E.L.; Sonwa, D.J.; Bele, Y.; Foahom, B.; Mate Mweru, J.P.; Wa Bassa, S.M.; Gapia, M.; Ngana, F.; Joe, A.E.; Masumbuko, E.M. (SAGE Publications, 2023)
Background and Research Aims: Agriculture through deforestation is an important threat to biodiversity conservation in the Congo Basin’s tropical forest. The policy challenge is not only to promote adaptation to perceived climate change but also to promote forest conservation. The aim of this study is to provide empirical evidence on the impact of farm-level investments in climate-smart agricultural practices related to conservation agriculture in some Congo Basin countries. The hypothesis is that property rights to land and trees play a fundamental role in governing the patterns of investment, forestland management for conservation, as well as in the profitability of agriculture. Methods: A Simulated Maximum Likelihood Estimation using a Mixed Logit model is used to test farmers’ choice of agricultural system and a farmland value model for each agricultural system which includes determinants of tenure or property rights, climate, soils, and socioeconomic variables such as education and gender. The data was collected from more than 600 farms covering 12 regions and 45 divisions in 3 countries, Cameroon, the Central African Republic and the Democratic Republic of Congo. Results: Farmers choose one of three agricultural systems to maximize farm profit mindful of the current tenure regime and environmental conditions. Conservation agriculture techniques within climate-smart practices show benefits for smallholder farmers through improvements in soil health, soil moisture retention and enhanced crop yields. The rights to access, withdraw, manage, as well as exclude others from land and trees affect both the farmers' choice of system and the profit earned from the chosen system. Conclusion: Farm-level investments improve farm incomes and enhance conservation effort for farmers perceiving climate change. Implications for Conservation: Climate change adaptation through planting of trees improves soil stability, restores ecosystems and creates a safe haven for biodiversity. Secure land tenure promotes better forestland management and reduces land degradation in vulnerable communities.